Towards microalga-based superfoods: heterologous expression of zeolin in Chlamydomonas reinhardtii - Perozeni, Federico; Pivato, Matteo; Angelini, Margherita; Maricchiolo, Elisa; Pompa, Andrea; Ballottari, Matteo (Frontiers in Plant Science, 2023)
Microalgae are unicellular photosynthetic organisms that can be grown in artificial systems to capture CO2, release oxygen, use nitrogen- and phosphorus-rich wastes, and produce biomass and bioproducts of interest including edible biomass for space exploration. In the present study, we report a metabolic engineering strategy for the green alga Chlamydomonas reinhardtii to produce high-value proteins for nutritional purposes. Chlamydomonas reinhardtii is a species approved by the U.S. Food and Drug Administration (FDA) for human consumption, and its consumption has been reported to improve gastrointestinal health in both murine models and humans. By utilizing the biotechnological tools available for this green alga, we introduced a synthetic gene encoding a chimeric protein, zeolin, obtained by merging the γ-zein and phaseolin proteins, in the algal genome. Zein and phaseolin are major seed storage proteins of maize (Zea mays) and bean (Phaseolus vulgaris) that accumulate in the endoplasmic reticulum (ER) and storage vacuoles, respectively. Seed storage proteins have unbalanced amino acid content, and for this reason, need to be complemented with each other in the diet. The chimeric recombinant zeolin protein represents an amino acid storage strategy with a balanced amino acid profile. Zeolin protein was thus efficiently expressed in Chlamydomonas reinhardtii; thus, we obtained strains that accumulate this recombinant protein in the endoplasmic reticulum, reaching a concentration up to 5.5 fg cell-1, or secrete it in the growth medium, with a titer value up to 82 µg/L, enabling the production of microalga-based super-food.